Traffic Engineering by the Traffic Unit of Cirebon Police Resort - Irsan, Muhamad Hatta (Advances in Police Science Research Journal, 2024)
This research is motivated by the frequent occurrence of traffic jams on Jalan Cirebon-Palimanan. Satlantas Cirebon Police has made various efforts by conducting traffic engineering which is expected to overcome congestion and the creation of kamseltibcar then on the road. Therefore, a study was conducted which aimed to determine the implementation of traffic engineering on the Cirebon-Palimanan road conducted by the Cirebon Police Traffic Unit. In analyzing, the writer uses theories and concepts, among others, Traffic Engineering Management Theory, Traffic Flow Smoothness Concept, Decision Grabbing Concept, and Planning Function Concept. Through a qualitative approach, data will be collected and subsequently analyzed inductively with reference to conditions on the ground. Through a qualitative approach, it is also able to get the meaning and definition of this research by being descriptive as well as pressing on the process that runs from the results. The results of the study are not in the form of numbers, but provide information data that is able to significantly solve the problem that the implementation of Traffic engineering is able to create smooth traffic flow. Analysis of the results of the implementation of Traffic engineering shows that the management and traffic engineering activities are not optimal, especially at the planning stage, namely the identification and analysis of the volume, the estimated volume of vehicles coming and the supervision stage in the form of indirect law enforcement actions through electronic media. The research findings show that the implementation of Traffic Engineering operations is already quite good with the fulfillment of the indicators contained in PP Number 32 of 2011. Based on the results of the study, the authors suggest that to keep on doing the traffic engineering model, action must be taken using electronic media and in coordination with other agencies, a proposal is made in the form of making parking bags in the road area.